Seroepidemiology of Camel Brucellosis in and around Dire Dawa, Eastern Ethiopia - Hika Waktole; Mohammed Aden; Hagos Ashenafi (Veterinary Medicine International)
Brucellosis is an infectious disease in domestic and wild animals with serious zoonotic and economic implication in humans, being more severe in developing countries. The disease is highly prevalent in cattle, camels, and small ruminants in pastoral and agro-pastoral areas in Africa. Here we have investigated the seroepidemiology of camel brucellosis in and around Dire Dawa, eastern Ethiopia, using a cross-sectional study design to determine the seroprevalence of the disease and to identify risk factors that would facilitate the transmission of zoonotic diseases to humans. This study involved testing 350 serum samples from camels and interviewing 120 livestock owners. The modified Rose Bengal plate test (mRBPT) and the complement fixation test (CFT) were used as screening and confirmatory tests, respectively. The overall sero-prevalence of camel brucellosis was found to be 8.3% and 2% using mRBPT and CFT tests, respectively. Among the risk factors assessed, only abortion and body condition disclosed a statistically significant difference p<0.05 with regard to the seropositivity of camel brucellosis. Camel brucellosis is prevalent in eastern Ethiopia and there is a need to execute well-organized disease control and prevention programs and exercise public health education to scale up awareness of the community towards the disease.